IDENTIFICATION AND MOLECULAR CHARACTERIZATION OF BOVINE HERPERVIRUSES (BoHV) DNA TERMINASE PARTIAL GENE IN ACEH CATTLE - Prayitno, Lilik; Saepuloh, Uus; Mayasari, Ni Luh Putu Ika; Faisal, Faisal; Ayuningsih, Ellis Dwi; Pamungkas, Joko Pamungkas (Universitas Syiah Kuala, 2017)
Bovine Herpesvirus (BoHV) is a member of Herpesviridae family that acts as pathogenic virus causing infectious bovine rhinotracheitis (IBR) among cattles, resulting in economic loss for cattle industry. BoHV-1 infection in cows is closely related to abortion, respiratory infection, reduced milk production, infertility, and low birth weight. The aim of this study was to identify and characterize the molecular of BoHV-1 and other virus types, as well as the possible presence of other Herpesviridae family using PCR to amplify DNA terminase gene. Four out of 210 nose swab samples were positive for herpes virus on DNA terminase gene. Further characterization of samples showed 99-100% similarity to BoHv-1 and BoHV-6 sequence. Genetic distance between genera BoHV-1 and BoHV-6 is 0.518 and within genera was 0.001 and 0.044. According to phylogenetic tree analysis of DNA terminase gene, the analyzed sequence clustered into 2 genera, namely Varicellovirus which is identical to BoHV-1 and Macavirus which is identical to BoHV-6. The study provides scientific information on molecular characteristics of Herpesviridae family, especially BoHV-1 which is prevalent in Indonesia with the highest density in the central ranches in Aceh province